4D measurements of biological and synthetic structures using a dynamic interferometer. (16th December 2017) - Toto-Arellano, Noel-Ivan
Abstract: Considering the deficiency of time elapsed for phase-stepping interferometric techniques and the need of developing non-contact and on-line measurement with high accuracy, a single-shot phase-shifting triple-interferometer (PSTI) is developed for analysis of characteristics of transparent structures and optical path difference (OPD) measurements. In the proposed PSTI, coupled three interferometers which generate four interference patterns, and a polarizer array is used as phase shifters to produce four spatially separated interferograms with π/2-phase shifts, which are recorded in a single capture by a camera. The configuration of the PSTI allows dynamic measurements (4D measurements) and does not require vibration isolation. We have applied the developed system to examine the size and OPD of cells, and the slope of thin films